Pola Perkembangan Hukum Islam di Indonesia dan Tantangannya - Kholidah, Kholidah (Jurnal EL-QANUNIY: Jurnal Ilmu-Ilmu Kesyariahan dan Pranata Sosial, 2024)
The development of Islamic law in Indonesia is formed in two patterns, namely cultural patterns and structural patterns. Cultural or non-legislative patterns are played out by ulama, kyai and also Islamic mass organizations. They increase the implementation of sharia in a button up, adaptive and persuasive manner in society. Meanwhile, the structural pattern or also called the constitution is played by the political elite. They try to implement Islamic values and Islamic legal norms into national law. Both cultural patterns and structural patterns each contribute and the two cannot be separated. Even so, the existence of Islamic law in Indonesia faces many challenges. The biggest challenge comes from Muslims themselves. Muslims in general still have very low legal awareness, starting from politicians as proponents of legislation and the public as users. This picture was obtained through secondary data from three legal materials, namely primary legal materials, secondary legal materials and tertiary legal materials. These legal materials are sourced from literature using a historical approach.